All Days 2002
DOI: 10.4043/14304-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Draft Semisubmersible with a Retractable Heave Plate

Abstract: Gulf of Mexico deep water oil fields present challenges to the offshore industry. Large fields require heavy drilling and production topsides which favor inshore deck installation, hook-up and commissioning in order to reduce time, costs and risks associated with carrying out such operations offshore. Harsh environments require that the motions of the structure be small to allow the use of dry trees and SCRs. A new system, called the DPS 2001, has been developed, which is a deep draft semisubmersible with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The deep draft can decrease the platform heave motion. Bindingsbø (2002) indicated that the heave and pitch RAOs of the deep draft semi-submersible platform are 50% less than those of the original semi-submersible platform; Halkyard (2002) improved the structure of deep draft semi-submersible platform, and demonstrated the structure of the DPS platform (Fig.3), which is similar to the Truss-spar platform (Fig.4). The heave-plate of a DPS platform, which generates huge added mass and viscous damping in platform heave motion, can rise to the bottom of the hull under transit conditions, and descend to 100 m below the sea surface under operating and survival conditions as a rigid member connected to the hull.…”
Section: Introductionmentioning
confidence: 92%
“…The deep draft can decrease the platform heave motion. Bindingsbø (2002) indicated that the heave and pitch RAOs of the deep draft semi-submersible platform are 50% less than those of the original semi-submersible platform; Halkyard (2002) improved the structure of deep draft semi-submersible platform, and demonstrated the structure of the DPS platform (Fig.3), which is similar to the Truss-spar platform (Fig.4). The heave-plate of a DPS platform, which generates huge added mass and viscous damping in platform heave motion, can rise to the bottom of the hull under transit conditions, and descend to 100 m below the sea surface under operating and survival conditions as a rigid member connected to the hull.…”
Section: Introductionmentioning
confidence: 92%
“…Deep draft semi-submersibles and those with heave mass traps have been shown to have suitable motions for dry trees, but as of this writing, they have not been employed (Le Guennec et al, 2002;Halkyard et al, 2002). The response for two ship shaped hulls of differing length and displacement are shown in fig.…”
Section: Motionsmentioning
confidence: 99%
“…Deck installation requires an offshore heavy lift, floatover, or a scheme for self-installation (LeGuennec et al, 2002;Halkyard et al 2002). While tall semi-submersibles have stability problems while submerging, a permanently sited unit would not require any deck variable load during installation and certain permanent deck payload may be absent.…”
Section: Chaptermentioning
confidence: 99%
“…As the semi-submersible platform has been widely used in recent years, the studies in this field are increasing: Morch and Moan (1985) compared the calculated and measured the wave-induced motion of a moored semi-submersible platform; Soylemez (1995) tested the motion of a twinhulled semi-submersible platform; Wu (1997) simulated the motion response of semi-submersible platform and mooring forces in regular waves by numerical method; Soylemez (1998) considered the combined action of wind, waves and current on semi-submersible platform, and simulated platform motion response with the method of time domain analysis, with the numerical results agreeing with their experiment; Bindingsbø (2002) studied the hydrodynamics of semi-submersible platform, his numerical results show that the hydrodynamics of a deep draft semi-submersible platform is better than that of the normal type; Halkyard et al (2002) designed a retractable heave plate for deep draft semi-submersible platform, which overcame transitional difficulties and optimized the hydrodynamic performance by using a dry tree. Engineers and scientists in China also did lots of researches on semi-submersible platform: Chen (1997) calculated the motion response and mooring line forces of a moored semi-submersible under wave action; Wang (2007) analyzed the motion performance of four kinds of semi-submersible platforms, and selected the suitable configuration for South China Sea environment.…”
Section: Introductionmentioning
confidence: 97%